Predictive Value of Red Blood Cell Distribution Width, Mean Platelet Volume and Platelet Distribution Width in Children with Acute Appendicitis - Jelena Antić; Radoica Jokić; Svetlana Bukarica; Ivana Lukić; Dejan Dobrijević; Goran Rakić; Miloš Pajić; Veličko Trajković; Marina Milenković (MDPI AG, 2021)
Background and Objectives: Acute appendicitis in pediatric patients is one of the most common surgical emergencies, but the early diagnosis still remains challenging. The aim of this study was to determine the predictive value of Red blood cell distribution width (RDW), Mean platelet volume (MPV) and Platelet distribution width (PDW) in children with acute appendicitis. Materials and Methods: This study was a retrospective assessment of laboratory findings (RDW, MPV, PDW) of patients who underwent surgical treatment for acute appendicitis from January 2019 to December 2020. Result: During this period, 223 appendectomies were performed at our Institute. In 107 (43%) cases appendicitis was uncomplicated, while in 116 (46.6%) it was complicated. WBC and RDW/MPV ratio were significant parameters for the diagnosis of acute appendicitis with cut-off values of 12.86 (susceptibility: 66.3%; specificity: 73.2%) and 1.64 (susceptibility: 59.8%; specificity: 71.9%), respectively. WBC and RDW/RBC ratio were independent variables for the diagnosis of complicated appendicitis. The cut-off values were 15.05 for WBC (sensitivity: 60.5%; specificity: 70.7%) and 2.5 for RDW/RBC ratio (sensitivity: 72%; specificity: 52.8%). Conclusions: WBC is an important predictor of appendicitis and complicated appendicitis. RDW, MPV and PDW alone have no diagnostic value in pediatric acute appendicitis or predicting the degree of appendix inflammation. However, the RDW/MPV ratio can be an important predictor of appendix inflammation, with higher values in patients with more severe appendix inflammation. RDW/RBC ratio may be an important predictor of complicated appendicitis.